Kualitas Aparatur, SIMDA – BMD, Regulasi Dan Pengendalian Internal Terhadap Pengelolaan BMD - Rahmadhani, Fitrah; Ariani, Ria (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
The purpose of this study was to examine and analyze the effect of the quality of the apparatus, regional management information system - regional property (SIMDA-BMD), regulation, and internal control on the quality of regional property management. The population in this study were all officials/officers who carried out the task of managing Regional Property at the Regional Work Units (SKPD) within the Bukittinggi City Government which were located in 29 Regional Apparatus Work Units (SKPD). The sampling technique used slovin technique and obtained a minimum number of respondents as many as 80 respondents and questionnaires filled out by 95 respondents, consisting of goods manager, goods manager assistant, assistant goods manager, regional property administration officer, officer/officer managing goods and stock. goods management officer/officer. The type of data used in this research is to use primary and secondary data, by using questionnaires and literature study. Data analysis in this study using Smart PLS. The results showed that: The quality of the apparatus has a positive effect on the quality of the management of regional property, regulations have a positive effect on the quality of the management of regional property, the regional management information system - regional property (SIMDA-BMD) has a positive effect on the quality of the management of regional property, and control internal has a positive and significant effect on the quality of the management of regional property.